Field assessment of old jetty in Malaysia - Tan, Joo Ee (2016)
Malaysia being a maritime country now faces the problem of lack of knowledge on how to assess the performance of old marine structure from available local practitioners. The existing guidelines adopted are still too complicated to be applied in engineering practice. There is an urgent need for a simple yet reliable method for assessing old structures. The project report presents detailed investigation findings on 68-year-old jetty facility which is still in service in northern part of Peninsular Malaysia to assess its structural condition. The objective of the report is to develop a practical assessment programme, to determine the long term relation between the rates of structure deterioration by measurements of material properties, and to determine the remaining service life of the jetty. A combination of direct tests and non-destructive tests such as concrete core compression test, rebound hammer test, carbonation tests, chloride ion ingression test and steel pile thickness measurement were performed. Direct testing on concrete cores has indicated the approximate remaining compressive strength of 33.5N/mm2. The result from the rebound hammer tests found that the Main Jetty’s equivalent compressive strength was 32 N/mm2 which is below present marine structural standard of minimum 50 N/mm2. The close approximation of the results shows that field tests using NDT can produce sufficiently adequate results for assessment of marine structures as long as the results of the NDT have been validated. Carbonation tests on the concrete cores shows that the 68-year-old jetty is not experiencing significant detrimental effects from carbonation. From observation of the core indicates that carbonation will remain within the concrete structure even after repair works unless concrete section affected by carbonation is completely removed. Chloride ion ingression is an observation of long term exposure effects to aggressive environment. The ingression of chloride is influenced by the location of the structure. It is found that the South Mooring Dolphin age 59 year old has shown high chloride content beyond the concrete cover and is therefore at higher risk of exposure to chloride induced corrosion. Steel thickness measurement is for assessing the critical steel pile member of the jetty facility where reduction of steel thickness is an indication of mass loss which is related to the capacity of the piles to carry load. As a conclusion, field assessment tests proposed in this report is simple yet produces reliable results for assessment of structures.